Alteration of the retinotectal map in Xenopus by antibodies to neural cell adhesion molecules. - Fraser, S E (1984)
The neural cell adhesion molecule (N-CAM) mediates neuron-neuron adhesion, is ubiquitous in the nervous system of developing and mature vertebrates, and undergoes major alterations in both amount and distribution during development. Perturbation of homophilic (N-CAM to N-CAM) binding by univalent fragments of specific anti-N-CAM antibodies has previously been found to alter neural tissue patterns in vitro. To show that significant alterations can also occur in vivo, antibodies to Xenopus N-CAM were embedded in agarose microcylinders and implanted in the tecta of juvenile Xenopus laevis frogs that were undergoing regeneration of their retinotectal projections; 1 week later, the effects of implantation on the projection pattern from the optic nerve were determined. Both polyclonal and monoclonal antibodies to N-CAM distorted the retinotectal projection pattern and greatly decreased the precision of the projection; these alterations recovered to near normal after an additional 3 weeks. Similar but smaller effects were obtained when normally developing froglets received tectal implants. In control animals, implants of immunoglobulins from preimmune serum and monoclonal antibodies not directed against N-CAM had little or no effect on the pattern. The results suggest that neuronal adhesion mediated by N-CAM is important in establishing and maintaining the precision and topography of neural patterns.